IMPROVING THE READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMPN 2 TELUK KUANTAN THROUGH TASK-BASED LEARNING METHOD - Ami Khairita Ramlis; Hadriana Hadriana; M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to find out whether or not the use of Task-Based Learning method can improve the reading comprehension of the second year students of SMPN 2 Teluk Kuantan. The type of the research is a classroom action research. The subject was class VIII5 which consists of 31 students. Test and observation sheets were used as instruments to collect the data. Test used to measure the students’ progress in every cycle during the classroom action research. This test consisted of pre-test and post-test. Observation sheets used to observe the teacher’s and students' activities in the classroom. The level of achievement in this research was 75, based on the standard minimum criteria of achievement of English subject in SMPN 2 Teluk Kuantan. The research finding showed that the implementation of Task-Based Learing method could improve the reading comprehension of the students at the first and second cycle. Based on the data analysis, the students’ scores improved from 59,03 in pre-test to 77,90 in post-test. Thus, the implementation of Task-Based Learning method could improve the reading comprehension of the second year students of SMPN 2 Teluk Kuantan.Key Words: Task-Based Learning Method, Reading Comprehension